Cross National Patterns of Retirement and Poverty Among Men and Women in the 1980 s: Full Stop or Gradual Withdrawal? - Timothy Smeeding (Luxembourg Income Study (LIS), 1991)
This paper compares work stoppage and pension income receipt among various age men and women who are household heads. It finds surprisingly large differences in retirement patterns across age groups, nations and men and women during the 1980 s.
Keywords: 330